Food insecurity among Finnish private sector service workers and food pantry clients. (30th September 2020) - Erkkola, M; Uusitalo, L; Puputti, K; Saari, T; Jallinoja, P; Rahkonen, O; Nevalainen, J; Walsh, H
Abstract: Background: There is a paucity of comparable quantitative data on the prevalence and predictors of food insecurity in high-income countries. We applied the Household Food Insecurity Access Scale (HFIAS) to assess food insecurity among i) the Service Union United members; female-dominated, low-income employees of the Finnish private service sector, and ii) a convenience sample of Finnish food pantry clients. Methods: The HFIAS classification was based on 9 validated questions capturing respondents' perceptions on food scarcity and behavioural responses to food insecurity due to lack of resources during the past month. The resulting indicator categorized respondents as food secure, and mildly, moderately and severely food insecure. We performed cross-tabulations and regression models to assess if education, housing, self-perceived health, income, and resource scarcity associated with levels of food insecurity. In addition, gender, age, and self-perceived disadvantage were assessed among the food pantry clients. Results: Among the service workers (n = 6 573, 6% of those invited), 35% were food secure, 29% mildly or moderately food insecure, and 36% severely food insecure. The respective proportions were 28%, 26%, and 46% among the 129 food pantry clients. All assessed variables were associated to food insecurity status in the service workers (p < 0.01 for all). Among the food pantry clients, men (OR 1.60; 95% CI 1.09 − 4.80) and homeless/tenants in community rental units (OR 7.12; 95% CI 2.42 − 20.95) were most likely to experience severe food insecurity. Conclusions: Alongside the food pantry clients the majority of the service workers demonstrated some degree of food insecurity, with a considerable proportion being severely food-insecure. This predominantly low-income group is subject to rapid changes in the labour market and social security systems. The data demonstrated that well-known SES indicators and self-perceived health are linked to food insecurity. Key messages: Severe food insecurity was common among predominantly low-income private sector service workers and food pantry clients. Food insecurity is linked to SES indicators and wellbeing.